ASSESSING DIFFERENT DETERMINANTS INFLUENCING THE DEATH OUTCOME RESULTING FROM ACUTE CORONARY SYNDROME IN PATIENTS TREATED IN THE CORONARY UNIT OF THE GENERAL HOSPITAL IN VALJEVO, AND THEIR DIFFERENCES - Filipovic, Aleksandra; Jankovic, Janko (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Cardiovascular diseases are the leading cause of morbidity and mortality in most countries of the world and are responsible for the death of 17.9 million people per year and for 11.8% of total DALYs. In Serbia, acute coronary syndrome (ACS) is the main cause of death among ischemic heart diseases, with a share of 49.9%. Aim: The aim of the study is to examine the association of various determinants (demographic, anthropometric, biological markers, risk factors, presence of comorbidities, and the pharmacotherapeutic approach) with the death outcome resulting from ACS patients treated at the Coronary Unit, as well as their differences. Materials and methods: This cross-sectional study included 384 adults with ACS, who were patients of the Cardiology Department with the Coronary Unit of the General Hospital in Valjevo, in 2020. The so-called Coronary Sheet was used as a research instrument. It was created, based on national needs, by the Institute of Public Health of Serbia "Dr. Milan Jovanović Batut", the Institute of Epidemiology, and the Cardiology Society of Serbia. This sheet is in the form of a questionnaire filled out by doctors working at the Coronary Unit, which is then submitted to the Institute of Public Health Valjevo. All respondents gave informed consent for anonymous participation in the research. The obtained data were analyzed using the methods of descriptive and analytical statistics, as well as the methods of univariate and multivariate linear regression. Results: The total sample consisted of 288 (75%) men and 96 (25%) women. The average age of patients who died of ACS was 72.9 ± 9.8 years, while the average age of patients who did not die of ACS was 65.0 ± 12.0 years. The difference was statistically significant (p < 0.001). Statistically significantly more patients who had lower values of both systolic and diastolic blood pressure, when admitted to hospital, died than those who had somewhat higher values of systolic and diastolic pressure at admission (p < 0.001). The mortality rate was lower for patients with ACS who were prescribed acetylsalicylic acid (p < 0.001), beta blockers (p = 0.003), ACE inhibitors (p < 0.001), and statins (p < 0.001) during hospitalization, while all patients whose therapy included inotropes as one of the drugs died (p < 0.001). Conclusion: Our research indicates the existence of a link between the examined determinants and the death outcome in patients suffering from ACS. It is necessary to improve the quality of data, maintain relevant and timely medical documentation and records, and continuously improve prevention programs, with the aim of reducing risk factors for the occurrence of ACS.